Risk factors for violent behaviors in patients with schizophrenia: 2-year follow-up study in primary mental health care in China - Huang, Zhuo-Hui; Wang, Fei; Chen, Zi-Lang; Xiao, Yao-Nan; Wang, Qian-Wen; Wang, Shi-Bin; He, Xiao-Yan; Migliorini, Christine; Harvey, Carol; Hou, Cai-Lan (Frontiers in Psychiatry, 2023)
Objective The consequences and impact of violent behavior in schizophrenia are often serious, and identification of risk factors is of great importance to achieve early identification and effective management. Methods This follow-up study sampled adult patients with schizophrenia in primary mental health care in a rural area of southern China, in which 491 participants completed a comprehensive questionnaire at baseline and the 2-year follow-up. Sociodemographic, clinical and psychological assessment data were collected from all participants. Paired sample T-Tests and the McNemar Test were performed to examine changes over the follow-up period. Generalized Estimating Equations (GEE) were used to analyze the risk factors for violent behavior. Results The results showed that about two in five community-dwelling patients with schizophrenia reported violent behavior in the past year. At follow-up, participants were significantly less employed, had more times of hospitalization, more psychotropic medication, and severer depressive symptoms, but had better health-related quality of life than at baseline. Use of clozapine and better insight into medication decreased the possibility of violent behavior, while more severe positive symptoms, insomnia, as well as use of second-generation antipsychotics other than clozapine, antidepressants and mood stabilizers increased the possibility of violent behavior. Conclusions Risk evaluation, prevention and management of violence in patients with schizophrenia are demanded in primary mental health care.